Gasification of eucalyptus in downdraft fixed bed to obtain synthesis gas - Edição, Tikinet (2023)
Gasification is a process where thermochemical conversion of biomass occurs yielding combustible gas or synthesis gas, depending on reaction circumstances, catalyst use or type of gasifier. The gasifier was fed in batches while air was continuously fed at flow rates between 5.62×10−3 mol/s and 9,96×10−3 mol/s. Air factors were in the range of 0.41 to 0.48. Mass and energy balances were realized, and thermochemical phenomena in the biomass bed were studied. Gas produced during the gasification process was analyzed every 20 minutes by gas chromatography with a Varian CP 3800 chromatographer equipped with a TCD detector. Peaks of 12,8% H2 and 14,8% CO and mean fractions of 5,36% H2 and 6,73% CO were registered at air flow of 9.96×10−3 mol/s. The gas produced had a higher calorific value of 1617 kJ/Nm3 and a lower calorific value of 1491 kJ/Nm3.